The Implementation of Mimicry Memorization Method for Novice Students in Learning Arabic Mufradat - Nor Afifah; Sunarto Sunarto; Moh. Fery Fauzi; Irma Anindiati; Talqis Nurdianto (Jurnal Al Bayan: Jurnal Jurusan Pendidikan Bahasa Arab)
Students of junior schools that have never studied Arabic language in elementary schools get more difficulties than the students that have studied it before. They are called novice students and must learn basic things of a new language such as mufradat because they must master, memorize, understand, and use it in order to have a good grip of mufradat, translate it, and able to use it in correct phrases and sentences. This research aimed to investigate the effectiveness of using mimicry memorization method for learning mufradat in Junior High School of Muhammadiyah and to investigate the extent which students improve memorization skills after using mimicry memorization method. The research was a quantitative method with a type of experimental research techniques. The data research was collected from observation, documentation, and oral tests techniques. The population of the study included 7th grade students of Junior High School Muhammadiyah 8 Batu and the samples were 7C students as experimental class and 7D students as control class. The results of research contributed that there was an increase 0.825 (large level) point in students’ memorizing ability after using mimicry memorization method. This method was effective to use for novice students in learning mufradat. A language teacher needs to consider this method for novice students. The study provides further support for the use mimicry memorization method for novice students in mastering new vocabularies.